Sulphated polysaccharide isolated from Sargassum vulgare: Characterization and hypolipidemic effects. (15th August 2017) - Kolsi, Rihab Ben Abdallah; Salah, Hichem Ben; Jardak, Neila; Chaaben, Rim; Jribi, Imed; Feki, Abdelfattah El; Rebai, Tarak; Jamoussi, Kamel; Allouche, Noureddine; Blecker, Cristophe; Belghith, Hafedh; Belghith, Karima
Highlights: Sulphated polysaccharide was successfully extracted from sargussum vulgare algae (SVSP). The chemical composition was established by FT-IR, GC–MS, NMR, HPLC. The monosaccharide composition showed the abundance of glucose sugar. An antioxydant activity in obese rats was determined. SVSP improve liver-kidney functions and testes architecture in obese rats. Abstract: A sulphated polysaccharide from brown algae Sargassum vulgare (SVSP) was extracted and examined with respect to chemical, structural characterization and hypolipidemic effects. SVSP consisted mainly of sulphate and total sugars with low levels of lipids and proteins. Its structure was studied by nuclear magnetic resonance (RMN), gas chromatography-mass spectrometry (GC–MS), infra-red spectroscopic, differential scanning calorimetry and X-ray diffraction analysis. Allowing us therefore to revealed that SVSP was composed of glucose, rhamnose, xylose, galactose, mannose and arabinose with XRD pattern that was typical for a semi-crystalline polymer and complexities of the spectra reflected its homogeneous structure. The administration of SVSP to obese rats is effective in lowering the body weight and inhibiting the lipase activity leading to notable regulation of lipid profile, increasing the activities of antioxidant enzymes, limiting lipid peroxidation; and protects liver-kidney functions proved by a decrease in the levels of toxicity parameters in blood, confirmed by histological study.